Pornochanchada: doce sabor da transgressão - Sales Filho, Valter Vicente (Comunicação & Educação, 1995)
The success of pornochanchada in Brazil, a type of motion picture made in the country during the 70's, is directly linked to the Brazilian society's moralism and conservatism.